2022
DOI: 10.1186/s12939-022-01631-6
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ opinions and experiences related to costs and reimbursements for medications in times of retrenchment: cross-sectional population surveys in 2015 and 2017

Abstract: Background Finland has universal coverage for prescription medications under the National Health Insurance. Eligibility schemes target higher reimbursements to individuals with chronic illness. Nevertheless, co-payments always apply, and austerity reforms implemented in 2016 and 2017 led to further increases in co-payments. We examined the extent to which people with chronic illness experienced financial difficulties in purchasing medications, how perceptions of fairness regarding the national … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 74 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Although ITS is considered to be a reliable design for evaluating the impacts of health policies, it does not provide protection against the impact of other events occurring at the same time [ 41 , 42 ]. Changes in reimbursements and medication prices may have an impact on medication use and prescribing practice in long term [ 32 , 43 ]. There are many factors influencing the treatment of BPSD, such as coping with BPSD of carers, care staff and patients with dementia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although ITS is considered to be a reliable design for evaluating the impacts of health policies, it does not provide protection against the impact of other events occurring at the same time [ 41 , 42 ]. Changes in reimbursements and medication prices may have an impact on medication use and prescribing practice in long term [ 32 , 43 ]. There are many factors influencing the treatment of BPSD, such as coping with BPSD of carers, care staff and patients with dementia [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested an increase in economic difficulties ( Aaltonen, Niemelä, & Prix, 2022 ; Rättö & Aaltonen, 2021 ; Lavikainen, Aarnio, Jalkanen, et al, 2020 ), negative developments in satisfaction of care ( Lavikainen, Aarnio, Niskanen, Mäntyselkä, & Martikainen, 2020 ), and impacts related to the consumption of type 2 antidiabetics ( Lavikainen, Aarnio, Jalkanen, et al, 2020 ; Lavikainen, Aarnio, Niskanen, et al, 2020 ) among individuals with type 2 diabetes after the reform. Regarding insulin consumption, a survey study found responders reporting increased insulin use due to cost ( Lavikainen, Aarnio, Niskanen, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%